Canine transposition as an alternative to trauma of the maxillary incisors: case report - María Salcedo Lara; Rocío Briones Rodríguez; María Biedma Perea; Beatriz Solano Mendoza (Dental Press Journal of Orthodontics)
ABSTRACT Objective: The present article aims at reporting the clinical case of a patient who suffered trauma at two years of age, causing almost complete apical displacement of the deciduous maxillary left central incisor and of the permanent incisor. Methods: Ectopia secondary to intrusion was minimized by surgical removal of the ectopic tooth, and the left permanent canine was submitted to orthodontic traction to replace the extracted tooth. Results: The treatment period lasted 36 months, resulting in correct occlusion and a good aesthetic outcome. Conclusions: Dental transposition carried out by means of orthopedic traction is a good alternative in cases of a very unfavorable ectopic tooth position.